(3eSGfjO CHj jMji aQGS Hf jMji GdecJH Gdchais - (3CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj, CHh fYje, J (B430 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN Jbi GdOjf CHh GdNWGH eMahX bGd (B: (3PcQ eG GfJgi EdjfG ef MOjK CHj jMji aQGS Hf jMji QhGjJg Yf YGeQ Hf TQGMHjd s
(3BNQgG (B:s
(3Yf GHf YeQ , bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3ef VQH YHOg Ch dWeg acaGQJg YJbg BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3HBNQgG SeGY efbhd ef fSNI GdCUd JGQjNg (B563 (3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs